The combination of sesamol and clofibric acid moieties leads to a novel potent hypolipidemic agent with antioxidant, anti-inflammatory and hepatoprotective activity. (15th July 2021) - Xie, Yundong; Liu, Jiping; Shi, Yongheng; Wang, Bin; Wang, Xiaoping; Wang, Wei; Sun, Meng; Xu, Xinya; Jiang, Haihui; Guo, Min; He, Yiyi; Ren, Cuicui; et al.
Graphical abstract: Highlights: CF-Sesamol was designed and synthesized, which showed a significant activity of reducing TG and TC. CF-Sesamol displayed potent antioxidant, anti-inflammatory and hepatoprotective effects. The hepatoprotective mechanism was through the Nrf2/NF-κB signaling pathway. Abstract: Oxidative stress and inflammation have been considered the main factors in the liver injury of clofibrate (CF). To obtain a novel antihyperlipidemic agent with antioxidant, anti-inflammation and hepatoprotection, the combination of sesamol and clofibric acid moieties was performed and achieved sesamol-clofibrate (CF-Sesamol). CF-Sesamol showed significant hypolipidemia effects in hyperlipidemia mice induced by Triton WR 1339, reducing TG by 38.8% ( P  < 0.01) and TC by 35.1% ( P  < 0.01). CF-Sesamol also displayed an alleviating effect on hepatotoxicity. The hepatic weight and hepatic coefficient were decreased. The amelioration of liver function was observed, such as aspartate and lactate transaminases (AST and ALT), alkaline phosphatase (ALP) and total proteins (TP) levels. Liver histopathological examination showed that hepatocyte necrosis, cytoplasmic loosening, nuclear degeneration and inflammatory cell infiltration reduced obviously by treatment with CF-Sesamol. Related molecular mechanisms on hepatoprotection showed that CF-Sesamol up-regulated Nrf2 and HO-1 expression and down-regulated p-NF-κB p65 expression in hepatic tissues. CF-Sesamol has significant antioxidant and anti-inflammatory effects. Plasma antioxidant enzymes such as SOD and CAT increased, anti-lipid peroxidation product MDA decreased. The expression of TNF-α and IL-6 inflammatory cytokines in liver was significantly lower than that in the CF group. The results indicated that CF-Sesamol exerted more potent antihyperlipidemic effects and definite hepatoprotective activity partly through the Nrf2/NF-κB-mediated signaling pathway.